The Analysis Quality of Service and Patient Satisfaction Participants of Health BPJS in Interior Services in Hospital X of Kediri City - Nugraheni, Reny; Kirana, Gerardin Ranind (Journal of Global Research in Public Health, 2018)
Government through the Health Insurance Provider Board (BPJS Kesehatan) which is the incarnation of PT. ASKES, strives to realize a healthy Indonesia program. All walks of life are entitled to receive health insurance from the government through programs from the BPJS Health. Regional General Hospital X Kota Kediri is a hospital belonging to the Government of Kediri. Therefore, the Hospital of X Kota Kediri must open themselves to receive and serve all patients both BPJS patients and general patients with the best. In this research, the object of research is Hospital X of Kediri City. And carried out in March 2017 to May 2015. Samples taken were inpatients treated at Flamboyan room, Dahlia room, Anggrek room, Teratai room, Bougenville room, Melati room and Mawar room. 200 respondents. Based on the analysis of research results can be concluded that the existence of service quality relationship with patient satisfaction BPJS in service inpatient at HOSPITAL X Kediri. Given that patient visits at Hospital X are heavily influenced by patient satisfaction, the steps that should be taken by the hospital management is how to improve the quality of service